Development of an OpenFOAM solver for numerical simulations of shell-and-tube heat exchangers based on porous media model. (25th June 2022) - He, Shaopeng; Wang, Mingjun; Tian, Wenxi; Qiu, Suizheng; Su, G.H.
Highlights: An innovative OpenFOAM solver of shell-and-tube heat exchangers was developed. The coupling between porous media and drift flux two phase model was realized. The feasibility of new solver was validated by two international benchmarks. The key three dimensional thermal parameters of heat exchanger were achieved. Abstract: As one of the most widely used types of heat exchangers, the shell-and-tube heat exchanger (STHX) offers the advantages of being low-cost, easy to clean, and highly reliable under high pressure and temperature conditions. Generally, a large number of tube bundles are used in the STHX to increase the heat transfer capacity. The three-dimensional (3D) two-phase flow simulation of the STHX is made exceedingly difficult if the tube bundle region is full-size modeled. Therefore, simplified models and approaches are required to meet the urgent demands of STHX engineering numerical simulation, especially for 3D analyses. Herein, we have developed an OpenFOAM solver "PorousDriftFoam" suitable for the two-phase flow and the boiling heat transfer numerical simulation of the STHX. The porous media model was applied to simplify the tube bundle region and the drift-flux model (DFM) was adopted in the two-phase flow computational fluid dynamics (CFD) simulation for the STHX. The heat transfer tubes are regarded as the solid region of porous media, while the shell side is considered the fluid region. We calculate the coupling heat transfer between the tube and the shell sides and consider the resistance introduced by the heat transfer tubes and support plates in the STHX. Two international benchmarks, the FRIGG test and the MB-2 experiments, were selected to fully validate the solver. For the FRIGG experiment, the predicted void fraction stands in good agreement with the experimental data, with an average absolute error of 0.07 and an average relative error of 13.3%. For the MB-2 experiment, the predicted values of pressure drop and temperature fit well with the experimental data. The developed solver could be applied in the 3D two-phase flow and heat transfer numerical simulation of a typical STHX in the industry.